Magnetotransport study of the spin-orbit coupling in SrIrO3-based thin films - Pong, Hao Yang (Nanyang Technological University, 2020)
Unlike conventional studies on perovskite oxides of LaAlO_3/SrTiO_3, this study investigates the Rashba effect on LaMnO_3/SrIrO_3 thin films. Firstly, the number of interface layers were modulated and magnetotransport scans were used to characterize the Rashba effect and its modulations using the Iordanskii, Lyanda- Geller, and Pikus model. The magnetotransport scans revealed that the Rashba effect was enhanced as the number of interface layers increased. Secondly, to further investigate how the number of interface layers affect the magnetotransport, Hall studies were carried out and it was found that both LaAlO_3/SrIrO_3 contributed to the conduction by the two-carrier model which can be explained by interfacial electron accumulation effects. Further studies to explore strongly correlated interfaces can be key to exploiting the Rashba effect.